Integrating Culturally Responsive Teaching (CRT) and Pancasila Students’ Profile Strengthening Project to Teach Advertisement Text in Senior High School - Ihsani, Muwafiqul; Prastikawati, Entika Fani (International Journal of Research in Education, 2024)
On teaching advertisement text, the teacher found the opportunity to make students enthusiastic to learn advertisement text, namely by integrating it to Pancasila students’ profile strengthening project with the theme of entrepreneurship. This integrated educational approach is put into practice by pre-service English teacher of Teacher Professional Education program at Public Senior High School 14 Semarang on teaching advertisement text. The implementation of CRT optimized the theories of Gay (2018) and the strategy from Irizarry(2015). The researchers focused to map the local wisdom culture especially the traditional food of Central Java province, Indonesia. The aim of this study was to use the CRT approach to teach advertisement text by doing the collaboration with P5 project. In light of this, the qualitative descriptive technique was chosen for the research design. The populations of this study were 10th grade students of Public Senior High School 14 Semarang. The samples used in this study were 10th grade students of Public Senior High School 14 Semarang at X-9 class. The results of this research mentioned five stages namely preparing and conditioning the class, explaining the local food branding, presenting the draft of local food advertisement target, monitoring the progress, and performing the outcomes. This research also revealed that the integration of CRT in English subjects, especially advertisement text with Pancasila students’ profile strengthening project successfully encourage the cultural sensitivity, especially traditional food. The teacher favorably acts as a facilitator who knows and assesses the mapping of the students’ original culture.